Past, Present and Future of Agroforestry Systems in Europe - Mosquera-Losada, M R; Moreno, G; Pardini, A; McAdam, J H; Papanastasis, V; Burgess, P J; Lamersdorf, N; Castro, M; Liagre, F; Rigueiro-Rodríguez, A (Agroforestry - The Future of Global Land Use SE - 16, 2012)
Many traditional land-use systems in Europe involved agroforestry in the pre-industrial era, but, over the years, increased mechanization led to the develop- ment of increasingly specialized crop, animal and wood production systems. As a consequence, the area under agroforestry declined in many regions of Europe, and agroforestry systems became con fi ned to situations where understorey primary production is restricted due to cold temperatures (Boreal and Alpine areas) or drought (Mediterranean areas) and to plots that are hard to reach or too small for cultivation with modern machinery, as in Spain, Italy and the lower altitude mountain regions in southern and central Germany. On the whole, agroforestry continued to be practised only where it enabled farmers to obtain economic returns from lands that were otherwise relatively unproductive and mostly limited to silvopastoral practices. Since the mid-1990s, however, European policies have encouraged land management systems that combine production, environmental services (biodiversity, carbon sequestration, nutrient cycling and water quality) and social bene fi ts, and this has created a new interest in agroforestry systems. Today, the major agroforestry practices in Europe include silvopasture and silvoarable. However, the bene fi ts and opportunities offered by agroforestry can only be realized with substantial investments and coordinated efforts in research, education, knowledge transfer and appropriate national policies across Europe.
Keywords: environmental services; Policy; Silvoarable; Silvopasture

Silvoarable Systems in Europe – Past, Present and Future Prospects - Eichhorn, M P; Paris, P; Herzog, F; Incoll, L D; Liagre, F; Mantzanas, K; Mayus, M; Moreno, G; PAPANASTASIS, V P; Pilbeam, D J; Pisanelli, A; Dupraz, C (Agroforestry Systems, 2006)
Mixed systems of agriculture incorporating combinations of trees and crops have formed key elements of the landscape of Europe throughout historical times, and many such systems continue to function in the present day. In many cases they represent formerly widespread traditional systems in decline and a number have already become extinct or exist only in a threatened state. The causes are both practical and economic. The agricultural subsidy regime within the European Union is presently unfavourable towards silvoarable practices, which has been a major factor in their recent decline. The silvoarable systems of Europe can be split into two classes according to location – northern Europe and the Mediterranean. The latter contains not only a greater area of silvoarable cultivation, but also a greater diversity of systems due to the broader range of commercial tree and crop species grown. In general, the systems of northern Europe are limited by light, whilst those of the Mediterranean are limited by the availability of water. Mixed systems of agriculture present an opportunity for future European rural development and have the potential to contribute towards the increased sustainability of agriculture and enhancement of biodiversity, whilst preserving landscapes that are both culturally important and aesthetically pleasing. A better understanding of the legacy of traditional silvoarable systems, combined with the formulation of a consistent deﬁnition and speciﬁc European policy towards them will be invaluable in ensuring that the beneﬁts of mixed agriculture are fully exploited in the future.
Keywords: Dehesa; hauberg; intercropping; orchards; pre-vergers; Streuobst; Timber